1997
DOI: 10.1111/j.1467-9566.1997.tb00019.x
|View full text |Cite
|
Sign up to set email alerts
|

Thinking teams thinking clients: issues of discourse and representation in the work of health care teams

Abstract: The use of multi-disciplinary health care teams is an increasingly common aspect of service delivery in health care in Western countries. While the literature rehearses the putative benefits to practitioners and clients of such teams, there appears to be an absence of extensive evidence-based research on team practices to substantiate such claims. What evidence there is suggests that team work is in different ways problematic. This article is a progress report on a qualitative research project into the operati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 32 publications
1
45
0
Order By: Relevance
“…9,10 Explanations for poor interprofessional relationships include the lack of explicit, appropriate task and role definitions; the absence of clear leadership; insufficient time for team building; the "us-and-them" effects of professional socialization; frustration created by power and status differentials; and the vertical management structures for each profession. [11][12][13][14] As this evidence of error and quality problems accumulates, it is accompanied by a growing belief among policymakers that interprofessional relationships are important and must be improved. For reasons that remain unclear, policymakers are choosing to intervene in this relationship using one of two generic approaches.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Explanations for poor interprofessional relationships include the lack of explicit, appropriate task and role definitions; the absence of clear leadership; insufficient time for team building; the "us-and-them" effects of professional socialization; frustration created by power and status differentials; and the vertical management structures for each profession. [11][12][13][14] As this evidence of error and quality problems accumulates, it is accompanied by a growing belief among policymakers that interprofessional relationships are important and must be improved. For reasons that remain unclear, policymakers are choosing to intervene in this relationship using one of two generic approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Working as a team is influenced by individual characteristics of team members (gender, age, or ethnicity, years of service); professional affiliations; roles, norms and values; and interprofessional perceptions of team processes [25,33,[41][42][43][44][45]. In our attempt to articulate the dimensions that participant HCPs mentioned regarding work in teams and CC, we turned to a new theory by Gittell et al because it [30] highlights the interdependence and interconnectivity of healthcare workers to providing effective and quality care.…”
Section: Discussionmentioning
confidence: 99%
“…For example, research by McClelland and Sands (1993) found that a missing team member who was in a position of supplying a critical piece of information or perspective on a patient (the professional "voice") at a team meeting resulted in a negative effect on patient care. Opie (1997) similarly argues that the ways in which differing representations are made by different team members have a powerful effect on the team's options for action.…”
Section: Interprofessional Teamwork: Relationship To Others On the Teammentioning
confidence: 95%